Understanding learning and teaching : the experience in higher education - Prosser, Michael, 1949-; Trigwell, Keith (Buckingham[England] ; Philadelphia, PA : Society for Research into Higher education and Open university press, 1999)
This book is about: Learning and teaching in Higher education; A model for understanding learning and teaching in higher education; ...
Keywords: Case studies; Higher education; College teaching; College teaching -- Australia -- Case studies; Learning, Psychology of -- Case studies; Education, Higher -- Australia -- Case studies